THE USE OF E-BOOK TO IMPROVE READING COMPREHENSION AMONG YEAR 4 PUPILS - Bee Choo Yee; Nurul Syazana Zainuddin (Journal of English Education, 2018)
This is an Action Research of using the Story Jumper as an E-book to improve the reading comprehension among Year 4 pupils in one of the primary schools in Malaysia. The participants involved were twenty pupils consisting of seven males and thirteen females. Three data collection methods employed were pre-test and post-test, pupils’ work and teacher’s reflective journal. The findings showed that the use of E-book had increased the level of understanding in reading comprehension among the research participants. The mean for the pre-test and post-test had increased from 45.83 to 93.33. The pupils’ work indicated positive improvements in terms of their level of understanding and responses in reading. It was also found from the reflective journal that the research participants had participated actively in the learning process and their level of motivation was also increased. The implication is to use E-book in the teaching of reading skills among the primary school learners.